Varicella-Zoster Virus–Specific Immune Responses in Elderly Recipients of a Herpes Zoster Vaccine - Levin, M. J.; Oxman, M. N.; J. H. Zhang; Johnson, G. R.; Stanley, H.; Hayward, A. R.; Caulfield, M. J.; Irwin, M. R.; Smith, J. G.; Clair, J.; Chan, I. S. F.; Williams, H.; et al. (The Journal of infectious diseases, 2008)
BackgroundA double-blind, placebo-controlled trial that involved 38,546 subjects ⩾60 years old demonstrated efficacy of a high-potency live-attenuated Oka/Merck varicella-zoster virus (VZV) vaccine. The trial included an immunology substudy to determine the relationship of VZV-specific immune responses to vaccination and clinical outcome MethodsThe immunology substudy enrolled 1395 subjects at 2 sites where blood samples obtained prior to vaccination, at 6 weeks after vaccination, and at 1, 2, and 3 years thereafter were tested for VZV-specific cell-mediated immunity (VZV-CMI) by γ-interferon ELISPOT and responder cell frequency assays and for VZV antibody by glycoprotein ELISA ResultsVZV-CMI and VZV antibodies were significantly increased in vaccine recipients at 6 weeks after vaccination. The vaccine-induced increases in VZV-CMI persisted during the 3 years of follow-up, although their magnitude decreased over time. The magnitude of these VZV-specific immune responses was greater in subjects 60–69 years old than in subjects ⩾70 years old ConclusionsThe zoster vaccine induced a significant increase in VZV-CMI and VZV antibody. The magnitude and duration of the boost in VZV-CMI in vaccine recipients and the relationship of this boost to age paralleled the clinical effects of the vaccine observed during the efficacy trial. These findings support the hypothesis that boosting VZV-CMI protects older adults against herpes zoster and postherpetic neuralgia